Fabrication of Strontium Bismuth Oxides as Novel Battery-Type Electrode Materials for High-Performance Supercapacitors. (17th September 2018) - Han, Yinghui; Li, Le; Liu, Yunpeng; Li, Xue; Qi, Xiaohan; Song, Lili
Abstract : A simple and efficient process method for the preparation of strontium bismuth oxides (SBOs) via an impregnation-calcination method is presented. The synthesized active materials are characterized using X-ray diffraction, scanning electron microscopy, and X-ray photoelectron spectroscopy. The electrochemical performance of the as-synthesized SBO samples is observed to decrease gradually as the strontium content is increased from 25% to 50%. The SBO sample with a Sr/Bi ratio of 1 : 3 shows the highest specific capacitance of 1228.7 F g −1 (specific capacity of 204.8 mAh g −1 ) at a current density of 1 A g −1 and a good cycling stability (75.1%) over 3000 charge-discharge cycles. The improved performance of the supercapacitors can be attributed to the unique structural features resulting from the addition of appropriate portions of Sr, which supports high electron conductivity and rapid ion/electron transport within the electrode and at the electrode/electrolyte interface. All the results show that the SBOs have considerable potential for use as high-performance battery-type electrodes in supercapacitors.